Heat and mass transfer processes new developments and applications : special topic volume with invited peer reviewed papers only - Delgado, J. M. P. Q. (Diffusion foundations, 2015)
The purpose of this Volume is to provide a collection of recent contributions in the field of heat and mass transfer in porous media. It includes a set of new developments in the field of basic and applied research work on the physical and chemical aspects of heat and mass transfer phenomena in a porous medium domain, as well as related material properties and their measurements. This volume contents include both theoretical and experimental developments, providing a self-contained major reference that is appealing to both the scientists and the engineers